A Critique of Cultural Theory's Impossibility Theorem - NOWACKI, Mark (Institutional Knowledge at Singapore Management University, 2004)
Various proponents of Cultural Theory (CT) have claimed that CT's Impossibility Theorem, namely that there are precisely five viable ways of life, has been formally proved. In this paper, I (a) show that the Impossibility Theorem has not been formally proved and (b) present a refutation of the Impossibility Theorem. With regard to (a), the problem areas identified include a failure to take into account the analogical nature of their theory and also a failure to carefully consider the nature of the relationship between mathematical models and the empirical phenomena that they are supposed to model. With regard to (b), an empirically grounded description of a distinct, sixth viable way of life, here called the Philosophical way of life, is presented. Second, a general argument is presented that demonstrates the necessity of positing a sixth form of rationality and a sixth viable way of life in addition to the five rationalities and five ways of life recognized by CT.